Contestations Access to Agrarian Resources in Forest Area of Dodo Jaran Pusang, Sumbawa District, NTB - ., Fahrunnisa; Soetarto, Endriatmo (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTControl and management of forests by the Government often gives rise to conflicts with communities, especially those that still utilize forest resources for their lives. This condition also occurs in forest area of Dodo, Jaran Pusang (RTK. 64) in Sumbawa, West Nusa Tenggara. Conflicts in forest area of Dodo involve community in Lawin village and Lebangkar village, sub-district Ropang, local government and the PT Newmont Nusa Tenggara who gained the concession of mining around forest area of Dodo. This research was qualitative research with a descriptive case study strategy. This research explains that the Lebangkar and Lawin community still can access forest of Dodo, indicated by a pattern of economic relations, socio-cultural and ecological of the communities with forest. The community also is constantly working to build power through FKDEL, YEP, SPPT, and SKPT movement to maintain access in the forest of Dodo. On the other hand, the Government of Indonesia, Newmont Nusa Tenggara, Society Ropang, Ranan, Lebin and Johnny wanted to access the forest of Dodo. Every actor has a different way to get access. The difference in the strength of the actor causing relationship tension between concerned actors.Keywords: agrarian contestations, access, Forest of Dodo, Lebangkar, LawinABSTRAKKontrol dan pengelolaan hutan oleh pemerintah sering menimbulkan pertentangan dengan masyarakat, terutama yang masih memanfaatkan sumber daya hutan untuk kehidupan mereka. Kondisi ini juga terjadi di Kawasan Hutan Dodo, Jaran Pusang (RTK.64) di Sumbawa, Nusa Tenggara Barat. Konflik di Kawasan Hutan Dodo melibatkan masyarakat di desa Lawin dan desa Lebangkar, kecamatan Ropang, pemerintah daerah dan PT Newmont Nusa Tenggara yang memperoleh konsesi pertambangan sekitar Kawasan Hutan Dodo. Penelitian ini adalah penelitian kualitatif dengan startegi studi kasus deskriptif. Penelitian ini menjelaskan bahwa masyarakat Lawin dan Lebangkar masih dapat mengkases hutan Dodo yang ditunjukkan dengan pola hubungan ekonomi, sosial-budaya dan ekologi masyarakat dengan hutan. Masyarakat juga terus berupaya membangunpower melalui gerakan FKDEL, YEP, SPPT, dan SKPT untuk mempertahankan akses di hutan Dodo. Di sisi lain, pemerintah Indonesia, Newmont Nusa Tenggara, masyarakat Ropang, Ranan, Lebin dan Lantung ingin mengakses hutan dodo. Setiap aktor memiliki cara yang berbeda untuk mendapatkan akses. Perbedaan kekuatan aktor menyebabkan ketegangan hubungan antara aktor-aktor berkepentingan.Kata kunci: kontestasi graria, akses, Hutan Dodo, Lebangkar, Lawin